ANALISIS KESESUAIAN KOMPONEN RPP MATEMATIKA GURU UPT SPF SMP NEGERI 1 BIRUBIRU - Antonius KAP Simbolon; Rosmita Sari Siregar (Nusantara Hasana Journal, 2025)
This research is motivated by the fact that many teachers still prepare Lesson Implementation Plans (RPP) solely for administrative purposes, without considering their compliance with the provisions of Permendikbud Number 103 of 2014. The purpose of this study is to describe the level of suitability of the four RPP components prepared by mathematics teachers using the 2013 Curriculum at the SPF Technical Implementation Unit of SMP Negeri 1 Birubiru. The approach used is descriptive qualitative with the research object being four RPP documents on the absolute value material. The results of the analysis show that the average suitability of the RPP components reaches 77.11%, which is classified as "in accordance" with the 2013 Curriculum standards. This finding indicates that mathematics teachers at the school have a high awareness of the implementation of RPP preparation rules according to Permendikbud Number 103 of 2014.